EVALUATION OF VEHICLE HANDLING BY A SIMPLIFIED SINGLE TRACK MODEL - Petr Hejtmánek; Ondřej Čavoj; Petr Porteš (Perner’s Contacts, 2013)
This paper presents a simplified simulation method for investigation of vehicle handling behaviour using the single track model of automobile. The main aim of this approach is to create a simulation model which contains only very small number of parameters and still maintains sufficient accuracy. The procedures for determining the values of all the necessary parameters are briefly discussed, as is the validation process of the mathematical model against the measurements conducted during drive manoeuvres. On the basis of primary validation results, the model was slightly enhanced by the addition of new parameters.